Plan de manejo de desechos en las comunidades de la organización UNOPUCH para que contribuya a la conservación de los páramos, año 2023 - Chango Yucailla, Myriam Carolina (2023)
The objective of this investigation is to propose a Common Waste Management Plan for the communities of La Unión de Organizaciones and Pueblo Chibuleo (UNOPUCH) to contribute to the conservation of the páramos, year 2023, to carry out the study, a methodology with a qualitative approach, type of descriptive, bibliographical and field research. The information collected came from primary and secondary sources. A survey with closed questions was carried out on 73 directors and delegates of UNOPUCH. Within the baseline, the physical, biological and socio-cultural environment was identified. The environmental waste management plan contains proposed measures for both common waste and hazardous waste from agricultural activities. The population agrees that poor waste management is due to poor education and environmental culture, the waste that is mostly generated is plastic, and the San Francisco community is the largest generator of waste. Within the proposal is the creation of a waste segregation and collection center, which can be beneficial to promote the economy of the inhabitants of the different communities, thus creating an awareness of caring for the environment through recycling. Keywords: Conservation, waste, we stopped, management, UNOPUCH